Underthrusting and Pure Shear Mechanisms Dominate the Crustal Deformation Beneath the Core of the Eastern Himalayan Syntaxis as Inferred From High‐Resolution Receiver Function Imaging - Xu, Qiang; Ding, Lin; Pei, Shunping; Yuan, Xiaohui; Zhao, Junmeng; Liu, Hongbing; Liu, Hanlin; Li, Lei; Zuo, Hong (Geophysical research letters, 2022)
How the crust in the core of the Eastern Himalayan Syntaxis (EHS) deforms responding to the India‐Asia collision remains ambiguous. Here we present the first high‐resolution receiver functions image of crustal structure along a new NW‐SE trending dense nodal array crossing the core of the EHS. Two sets of low velocity zones (LVZs) are clearly observed: one with a flat style beneath the western Lhasa terrane and Higher Himalaya at 18–20 km depth and the other with two west‐dipping shapes below the western Yarlung‐Zangbo suture within 10–30 km depth. These LVZs caused by partial melting and aqueous fluids are disconnected, impeding the formation of crustal flow. A discontinuous east‐dipping intra‐crustal discontinuity and a sharp Moho offset of 7 km under the Aniqiao‐Motuo shear zone are identified, suggesting that the underthrusting of the Indian lower crust and pure shear mechanisms jointly dominate crustal deformation in the core of the EHS. Plain Language Summary The tectonic evolution of the Eastern Himalayan Syntaxis (EHS) involves complex tectonic activities such as collision, subduction, and rapid exhumation, making the EHS an ideal site for studying the dynamics of continental collision processes. Strong crustal shortening occurs during the formation of the EHS, but the specific mechanism that accommodates this crustal deformation remains unclear. In this study, we construct a novel seismic image of crustal structure with unprecedented details along a recently deployed dense nodal array that traverses the core of the EHS. We observe two unconnected groups of low velocity zones, which call into question the validity of the crustal flow model in the core of the EHS. Our observations indicate that the underthrusting of the Indian lower crust and pure shear mechanisms, rather than a model of vertically coherent deformation, account for the present crustal deformation in the core of the EHS. Key Points First high‐resolution image of crustal structure in the core of the Eastern Himalayan Syntaxis is constructed from P receiver functions Two disconnected groups of low velocity zones are observed in upper to middle crust, which prevents the development of crust flow An intra‐crustal interface and a Moho offset we find suggest that underthrusting and pure shear mechanisms dominate crustal deformation